Mainstreaming gender equality in Europe. A critical frame analysis approach - Verloo, Mieke (The Greek Review of Social Research, 2016)
This article analyzes implementation problems in gender mainstreaming as accentuated by a multi-level setting and assumes that one of the major factors affecting implementation problems is a discursive one. Against this backdrop a methodological approach is presented to study such divergences in policy frames on gender equality. Based upon recent literature, the article first outlines the necessity for a comparative methodology to analyze (gender equality) policy frames, and identifies some major problems in the construction of such methodology. The article then presents and explains Critical Frame Analysis as a promising methodological approach for studying and comparing the framing of gender inequality as a policy problem across Europe in a systematic way. Critical Frame Analysis builds upon social movement theory, gender theory and policy theory. This article can be considered to be an introduction to the special issue, as all articles refer to Critical Frame Analysis methodology as it has been used in the MAGEEQ research project.